A reference profile ontology for communities of practice. (1st January 2012) - da Silva, Joao L.T.; Ribeiro, Alexandre Moretto; Boff, Elisa; Primo, Tiago Thompsen; Viccari, Rosa Maria
Communities of Practice (CoP) integrate people in a group in order to learn in a collaborative way. It is necessary to establish in these communities a formal and standardised representation of the knowledge and interests that emerge from CoP. With this scenario in mind, this paper presents a reference ontology for a user profile representation in a CoP Framework (CoPF). The main idea of this framework is to provide virtual CoP for collaborative learning by using semantic web technologies. This work proposes a foundational ontology for a general profile to be used as a guideline to build a computational CoPF, which is semantic web compliant. In this paper we summarise a first proposition of the CoPF ontology development focusing on the ontological user profile. We also present the methodological aspects of the ontological CoPF and also illustrate a case study applying the ontological user profile.